Pengaruh Etika Konsumen Islami, Religiusitas, dan Paparan Kampanye Boikot Terhadap Keputusan Menikmati Film yang Terafiliasi Israel Dengan Niat Menikmati Film Sebagai Variabel Intervening: Studi Kasus pada Komunitas Pengguna Letterboxd di Indonesia - Ahsan Zanky Fikry Al Hamidy; Yan Putra Timur (Ikatan Da'i Indonesia, 2026)
This study aims to analyze the effect of Islamic consumer ethics, religiosity, and exposure to boycott campaigns on the decision to enjoy Israel-affiliated films, with the intention to enjoy films as an intervening variable, within the Letterboxd user community in Indonesia. The growing awareness among Muslim consumers regarding the geopolitical affiliations of entertainment products, particularly amid the Palestinian-Israeli conflict increasingly discussed on digital platforms, serves as the background of this research. This study employed a quantitative approach using an online survey questionnaire distributed to 159 respondents who are active Letterboxd users, Muslim, and residing in Indonesia. The independent variables include Islamic consumer ethics (X1), religiosity (X2), and exposure to boycott campaigns (X3), while the dependent variable is the decision to enjoy Israel-affiliated films (Y), with the intention to enjoy films (Z) as the intervening variable. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4 software, grounded in the Theory of Planned Behavior (TPB) by Ajzen (1991).The findings indicate that the intention to enjoy films significantly mediates the effect of Islamic consumer ethics on the decision to enjoy Israel-affiliated films through a full mediation mechanism. Conversely, the intention to enjoy films does not significantly mediate the effect of religiosity on the decision to enjoy Israel-affiliated films, suggesting that general religiosity alone is insufficient to directly drive avoidance of specific digital entertainment content. Boycott campaign exposure demonstrated the strongest mediating influence among all variables, establishing it as the most powerful predictor in shaping the intention and decision to enjoy Israel-affiliated films within the Letterboxd user community in Indonesia.